2006
DOI: 10.1111/j.1740-8261.2007.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Repeatability of Feline Echocardiography Using Conventional Echocardiography and Spectral Pulse‐wave Doppler Tissue Imaging Techniques

Abstract: The objective of this study was to determine the intraoperator, intraobserver, and interobserver repeatability in a series of conventional echocardiographic parameters and in some of the newer measurements of diastolic function, including color M-mode flow propagation velocity, isovolumic relaxation time and pulsed-wave Doppler tissue imaging velocities. Four healthy cats were each scanned five times over a 3-day period. The repeatability of these echocardiographic analyses was compared using Bland-Altman anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 33 publications
3
51
0
13
Order By: Relevance
“…Finally, we did not evaluate intra-operator variability. Poor repeatability has been reported in the acquisition of the velocities from the long-axis posterior wall and interventricular septum using pulsed TDI analysis (Simpson et al, 2007). Another study showed that the intra-examination variability was better under anaesthetised conditions (Chetboul et al, 2004), which was attributed to perfect immobility of the animal that improved repeatability of TDI measurements.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, we did not evaluate intra-operator variability. Poor repeatability has been reported in the acquisition of the velocities from the long-axis posterior wall and interventricular septum using pulsed TDI analysis (Simpson et al, 2007). Another study showed that the intra-examination variability was better under anaesthetised conditions (Chetboul et al, 2004), which was attributed to perfect immobility of the animal that improved repeatability of TDI measurements.…”
Section: Discussionmentioning
confidence: 97%
“…Spectral pulsed-wave TDI is a technique that measures myocardial velocity, which has good temporal resolution (Simpson et al 2007) and has been used to assess the velocities within the feline myocardium (Chetboul et Chetboul et al (2006a) using affected cats and carriers of dystrophin-deficient hypertrophic muscular dystrophy as a model of HCM, demonstrated that TDI could detect radial and longitudinal LVFW dysfunction in all cats even though none of the animals presented significant left myocardial hypertrophy. In this same study, those cats with mutations but without LVFW hypertrophy showed larger longitudinal TDI isovolumic relaxation times, longitudinal TDI E'/A' ratios less than 1 at the base and radial TDI E'/A' ratios less than 1 in the sub-endocardium and subepicardium, as well as reduction of systolic longitudinal myocardial velocities at the heart base and apex, when compared with healthy cats.…”
Section: Echocardiographic Approachmentioning
confidence: 99%
“…The TDI is an echocardiographic technique that allows quantification of global and regional myocardial function from measurements of myocardial velocities in real time (Chetboul 2002, Simpson et al 2007, Chetboul 2010. Pulsed-wave and colour M-mode are TDI techniques that have been demonstrated to be sensitive tools to detect even mild forms of HCM, providing an early diagnosis of the disease (MacDonald et al 2006, Koffas et al 2006, Koffas et al 2008.…”
Section: Echocardiographic Approachmentioning
confidence: 99%
See 2 more Smart Citations